Contextual factors and organizational commitment: Examining the mediating role of thriving at work (2019)
Thriving at work refers to a psychological experience of learning (cognitive dimension) and vitality (affective dimension) to the workplace. Based on the Social Exchange Theory and the Socially Embedded Model of thriving, the purpose of this research is to observe whether contextual variables such as fairness perception, trust, and managerial coaching are related to affective organizational commitment and to examine if thriving at work plays a mediating role in these proposed relationships. Data was collected in two waves over a one-month time period from 936 employees of diverse public and private sectors. Strong empirical evidence was found for all direct and indirect hypothesized relationships through Smart PLS 3.0 (SmartPLS GmbH, Bönningstedt, Germany, 2015). The implications of the findings are also discussed. © 2019 by the authors.